Significados do trabalho informal em Luanda: luta, coragem e persistência nas vozes dos jovens migrantes - Samba, Simão João (2012)
This work was carried out in Luanda, capital of the Republic of Angola, from the experience of work and life of young migrants involved in informal work in Luanda, specifically the street vendors. The objective was to analyze the meanings that young migrants involved in informal work in Luanda, attach to their experiences as well as the reasons that led then to the involvement of such activities. Understand these informal activities and understand as well how it contribute to overcame their poor working conditions and the survival of this young vendors, since they live mostly in a context marked by extreme poverty, vulnerability, exclusion and social inequality. It is understood that the knowledge and analysis of the meanings of these young people attribute to their stories and experiences, as well as the reasons for their involvement in informal activities, current issues are social important, given the few or almost no studies that address this reality from the view of who is involved in it. It is a qualitative study, based on Marx's social theory, specifically in the analytical perspective of dialectical materialism critical. The study included 16 young migrants, informal workers in Luanda, of both sex, aged between 18 and 35 years. We used as data collection technique of participant observation and systematic interviews and group oriented script prepared in advance, both complemented by bibliographic and documentary research. A field diary was used to record the necessary information, which later contributed to the analysis of information obtained and presented in this paper. The testimonies of this young people pointed out the alternative of the informal work as a mean of survival strategy, which cater to the lack of jobs that could absorb them. On the other hand, showed that there is a crackdown on this type of work, by the state, without the state providing alternatives to enable them to survive. It also pointed out that those young people do not have the informal work as a project of their life; many of them are doing this informal work and studying at the same time, which they believe could open employment opportunities for then. The migration of these young people to the capital in search of a better living conditions, work, security, protection and opportunity, was mainly due to the war and lack of investment in rural areas. It is concluded that informal work is an alternative and strategy of those young people to overcome the lack of jobs and the multiple losses and miseries that they go through their life stories and trajectories, including the lack of conditions to keep up with dignity and provide the essential to their children and dependents. These situations highlight the need to think in social and public policies capable of achieving the desires, aspirations and expectations of these individuals and ensure their protection, while construction of new spaces of possibilities and ways of life of those who are deprived of their fundamental rights